Uji Efektivitas Ekstrak Etanol Biji Mahoni (Swietenia Mahagoni (L.) Jacq) Sebagai Antihipertensi terhadap Tikus Putih Jantan Galur Wistar: Effectiveness Test of Mahogany (Swietenia Mahagoni (L.) Jacq) Seed Ethanol Extract as Antihypertensive Against Wistar Strain Male White Rats - Miming Andika; Charissa Novita; Harry Ade Saputra; Rizqa Hasanah (LPPM Universitas Abdurrab, 2023)
Hypertension or high blood pressure is a condition where a person's blood pressure is above the normal limit, which is indicated by a systolic pressure above 140 mmHg and a diastolic pressure above 90 mmHg. This study aimed to determine the effectiveness of ethanol extract of mahogany seeds as an antihypertensive against male galur wistar white rats strain. The research was True Experimental with Pre-Test Post-Test Control Group Design, using male white rats as test animals divided into 6 groups, namely negative control group, positive control group, dose group (100, 200 and 400 mg/kgbw) and comparison group (Captopril 25 mg). The inducer used was 8% NaCl for 30 days. Blood pressure measurements were carried out using a CODA Non-Invasive Blood Pressure (NIBP) device. Data analysis using one-way ANOVA followed by the Bonferroni test showed that administration of mahogany seed ethanol extract had an effect on decreasing systolic, diastolic, mean arterial blood pressure and heart rate significantly (p<0.05). It can be concluded that the most effective dose of mahogany seed ethanol extract in lowering blood pressure (systolic, mean arterial and heart rate) was a dose of 200 mg/kgbw and for diastolic blood pressure the most effective was the comparison drug.